Germinação de sementes e desenvolvimento de plântulas em Paspalum notatum Flügge - Aguiar, Anderson Rossi de (2014)
Paspalum notatum, native grass biome Pampa, Rio Grande do Sul, has high forage value, but has difficulty germinating seeds with low viability. Inserted in this context are the promoters of germination and biomass, biostimulants stimulate® and bioagent Trichoderma spp. by mechanisms that influence the metabolism of action of the species. The present study investigated the promotion of seed germination and development of P. notatum. Through the Allium cepa test in ten treatments (four replicates per treatment), eight with metabolites of Trichoderma spp. and two controls in the absence of metabolites were selected isolates of trichoderma biological agent. The test of sanity, the identification of fungi associated with seeds used the methods of filter paper and plating on solid agar PDA (potato dextrose agar). With the in vitro technique of direct confrontation of the antagonist action on three fungal contaminants of highest incidence was observed. In a preliminary test, pre-treatment is selected to germination of P. notatum. Seed germination in greenhouse consisted of 16 treatments with four replicates, the control treatments, the three isolates, the stimulate®, the combination of each of the three isolates stimulate®, all with and without pretreatment, analysis of the data was through the Genes program. For reviews of morphogenesis, four were randomly chosen tillers per treatment, they monitored for the appearance and elongation and leaf senescence. This monitoring was performed two times per week. The top three trichoderma isolates selected in test A. cepa strain were 2B2, C1, 2B12. The removal of the seed coat structures of P. notatum was the pre-treatment showed the best performance with 34.5% twinned seeds. In the test of sanity the fungal genera Aspergillus, Curvularia, and Fusarium Geniculosporium were identified, isolated and 2B2 of Trichoderma spp. efficient for direct to these fungal genera confrontation. For the IVE (index emergency speed), the combination treatments of biological powder 2B12 isolated from trichoderma and biostimulating Stimulate® and only Stimulate® biostimulating with pretreatment and without pretreatment combination of biological powder isolated 2B2 Trichoderma with biostimulating Stimulate®, achieved the best results, with 14.48, 13.93 and 12.75, respectively. The biostimulating stimulate® promotes the rate of speed of emergence of seeds of P. notatum and the production of dry matter, the initial rate of elongation of the sheet (TAIF) positively interfere in the dry weight of shoots.